Methyladenosine Modification in RNAs: Classification and Roles in Gastrointestinal Cancers - Li, Qinghai; He, Weiling; Wan, Guohui (Frontiers in Oncology, 2021)
Cellular ribonucleic acids (RNAs), including messenger RNAs (mRNAs) and non-coding RNAs (ncRNAs), harbor more than 150 forms of chemical modifications, among which methylation modifications are dynamically regulated and play significant roles in RNA metabolism. Recently, dysregulation of RNA methylation modifications is found to be linked to various physiological bioprocesses and many human diseases. Gastric cancer (GC) and colorectal cancer (CRC) are two main gastrointestinal-related cancers (GIC) and the most leading causes of cancer-related death worldwide. In-depth understanding of molecular mechanisms on GIC can provide important insights in developing novel treatment strategies for GICs. In this review, we focus on the multitude of epigenetic changes of RNA methlyadenosine modifications in gene expression, and their roles in GIC tumorigenesis, progression and drug resistance, and aim to provide the potential therapeutic regimens for GICs.